2006
DOI: 10.1111/j.1471-6712.2006.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial work stress is associated with poor self‐rated health in Danish nurses: a test of the effort–reward imbalance model

Abstract: Nursing staff are exposed to stressful work load which in turn is associated with poor physical and psychological health, sickness absence and job exit. The effort-reward imbalance (ERI) model is a validated approach to measure chronic psychosocial work stress by identifying nonreciprocity between occupational efforts spent and rewards received, and has been found to predict poor health. The aim of this cross-sectional study (n = 367 nurses and nurses aides) was first to test the psychometric properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
3
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 48 publications
11
93
3
5
Order By: Relevance
“…In relation to the nursing team, we can say that the results presented here are in agreement with studies that used the ERI model as a resource to analyze organizational environments (18)(19) .…”
Section: Methodssupporting
confidence: 80%
“…In relation to the nursing team, we can say that the results presented here are in agreement with studies that used the ERI model as a resource to analyze organizational environments (18)(19) .…”
Section: Methodssupporting
confidence: 80%
“…Moreover, it is one of the most stressful factors within a healthcare organization; as any other stressor usually moderates staff's job satisfaction and creates turnover intentions (Kooker et al, 2007). Occupational or work-related stress has a direct effect on all nursing members of the work force, might it be of long, short or intermediate duration, or a once off experience (Weyers et al, 2006). High workload is a key job stressor of nurses in a variety of care settings, such as ICUs (Carayon & Gurses, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Over time the imbalance between efforts and rewards may increase susceptibility to illness thorough continuous experience of negative emotions and consequent strain (Siegrist et al, 2004). The effort/reward imbalance has proved effective in predicting several outcomes related to health and well-being (van Vegchel et al, 2005) among healthcare workers (van Vegchel et al, 2001;Hasselhorn et al, 2004;Bakker et al, 2000;Weyers et al, 2006). Moreover, according to the model there may also be individual differences in the experience of effort/ reward imbalance.…”
Section: Effort/reward Imbalance and Overcommitmentmentioning
confidence: 99%
“…Cardiovascular and musculoskeletal disorders were related to age, which was an expected finding considering their chronic nature, and also to overcommitment. In a review by van Vegchel et al (2005), four out of five studies found overcommitment to be associated with a higher incidence of cardiovascular disorders, while Weyers et al (2006) did not find any significant association between overcommitment and self-reported musculoskeletal complaints in Danish nurses. It is also interesting to note that rumination has been linked with cardiovascular and musculoskeletal disorders (Brosschot et al, 2006).…”
Section: Associations Between Risk Factors and Health Outcomesmentioning
confidence: 99%